RISK MANAGEMENT PRACTICES AND ADMINISTRATIVE EFFECTIVENESS OF SECONDARY SCHOOL PRINCIPALS IN TARABA STATE, NIGERIA (Scientific Journal of Educational Management, Research and law, 2026)
This study explores the impact of risk management practices on the administrative effectiveness of secondary school principals in Taraba State, Nigeria. The study focuses on risk identification, risk assessment, and stakeholder involvement as key components of risk management. A descriptive survey design was employed, with a sample of 300 principals (150 male and 150 female) purposively selected from a population of 1,245 principals in Taraba State. Data were collected using a researcherdeveloped instrument titled "Risk Management Practices and Administrative Effectiveness Questionnaire (RMPAEQ)," validated by experts and with a reliability coefficient of 0.78. Mean and standard deviation were used to address research questions, while independent t-tests were applied to test three null hypotheses at a 0.05 significance level. The findings revealed significant relationships between risk identification, risk assessment, stakeholder involvement, and administrative effectiveness. It was concluded that robust risk management practices enhance principals’ decision-making, resource allocation, and leadership effectiveness. Recommendations include regular training on risk management and fostering stakeholder collaboration to improve administrative outcomes.